LONG-TERM FERTILIZATION ALTERED LABILE SOIL ORGANIC CARBON FRACTIONS IN UPLAND SOILS OF CHINA - R. Nazia; F. Liang; S. Huang; B.Wang; M. Xu; J. Li; H. Gao; W. Zhang (Journal of Animal and Plant Sciences, 2019)
Labile soil organic carbon (SOC) plays key roles in the assessment of improving soil fertility and structure for agricultural land sustainability, but changes in labile SOC fractions at different soil profiles with long-term fertilization are limited. In this study, we investigated the effect of long-term fertilization on the labile SOC fractions with various potassium permanganate oxidizable C (KMnO4–C) concentrations at three different long-term experimental sites. Soil depths were 0-40cm at GZL and 0-100cm at ZZ and QY. The four fertilization treatments included cropping without fertilization (CK),inorganic fertilizer nitrogen, phosphorus and potassium (NPK), inorganic fertilizer with manure (NPKM) and inorganic fertilizer with straw (NPKS). Results showed that SOC storage in 0-20cm soil layer increased under all treatments in the order of NPKM > NPKS >NPK relative to CK at all sites except GZL (NPKM>NPKS, NPK). The SOC storage in whole soil profile was greater under all treatments in the order of NPKM >NPKS> NPK relative to CK at GZL, ZZ and QY. Moreover, long-term fertilization increased topsoil (0-20 cm)labile SOC storage pool which declined sharply with the increasing soil depth at each experimental site. The average SOC storage of less, mid and highly labile fraction in manure with balanced fertilizer (NPKM) increased by113.3, 183.7 and 274.5% at 0-40cm depth of GZL and by 153.4, 76.0, 67.6, 105.5, 129.8 and 118.7% at depth of 0-100 cm of ZZ and QY, respectively, as compared to CK. Consequently, this study suggested that the application of combined NPK with manure or straw can improve soil carbon storage and SOC liable fraction along soil profile across various upland region of China.
Keywords: Long-term fertilization ，labile soil organic carbon; soil depths